2011
DOI: 10.1007/s00464-011-2024-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic ventral hernia repair: Does primary repair in addition to placement of mesh decrease recurrence?

Abstract: Primary laparoscopic repair along with mesh placement for the management of ventral hernia was found to be effective in selected cases as evidenced by the low rate of recurrence when compared with conventional laparoscopic repair with mesh alone. Further retrospective and prospective studies, with larger patient enrollment, are warranted to confirm the benefit of this technique over traditional repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 18 publications
0
57
1
3
Order By: Relevance
“…Laparoscopic technique is basically a mesh repair; however, laparoscopic primary suture repair without prosthetic material has also been experienced (29). In contrast, Banerjee et al (30) compared the laparoscopic mesh placement without defect closure with laparoscopic suture and mesh in a clinical study and reported a slightly lower recurrence rate in the latter group, particularly for recurrent hernias.…”
Section: Which Repair Technique?mentioning
confidence: 99%
“…Laparoscopic technique is basically a mesh repair; however, laparoscopic primary suture repair without prosthetic material has also been experienced (29). In contrast, Banerjee et al (30) compared the laparoscopic mesh placement without defect closure with laparoscopic suture and mesh in a clinical study and reported a slightly lower recurrence rate in the latter group, particularly for recurrent hernias.…”
Section: Which Repair Technique?mentioning
confidence: 99%
“…After intra-abdominal placement of a mesh, the fascia defect is closed and mesh fixation is accomplished laparoscopically [11,12] . Using this HA-less tissue dissection is expected compared with the open procedure, therefore with lower risk of local complications [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…An inert mesh material such as polyvinylidene fluoride (PVDF) was used in the sandwich technique in 47 patients with promising low incidence of postoperative mesh-related infections [172] when compared to 3.6 % prosthetic infection with the use of ePTFE patches [164]. Primary laparoscopic Sugarbaker mesh placement with transabdominal suture on either side of the lateralized bowel was found to be effective in reducing the recurrence rate [169]; it could be performed in selected small parastomal hernias or some large ones to ensure adequate approximation of the edges prior to mesh deployment [175].…”
Section: Parastomal Incisional Herniasmentioning
confidence: 99%